Leading people the modern way : a case study on shared leadership in the German healthcare sector - Bierzynski, Markus (My University, 2012)
This thesis discusses leadership in team settings in the context of the German healthcare sector. The exploration of modern leadership styles answers the needs of today’s working force and the implications of the globalizing world. Consequently, the aim of the thesis is to elaborate a comprehensible leadership framework for team settings. Therefore, dimensions affecting leadership need to be explored and evaluated and their relationships assessed. An extensive literature review is conducted including the shared leadership, co-leadership and team leadership theory to build a preliminary framework. The dimensions are divided in enablers and facilitators. Since research is pretty scarce so far in this combined area a qualitative in-depth case study is used to answer the research question. The case study is composed out of interview data conducted at a healthcare company in Germany complemented by documentary data. Semi-structured interview type is used answering the needs of the study purpose. The analysis of the case study is supported by the data gathered during the study process. Firstly, the enablers’ impact on the leadership style are evaluated and their relationships towards each other. Secondly, the facilitators’ impact on the enablers is assessed. The analysis shows that sharing responsibility, autonomy, collaboration and commitment affect the leadership behaviour significantly. Furthermore, trust and communication are able to promote or decrease the efficiency of the identified enablers. In addition, personality is identified as a third facilitator impacting all other dimensions. In general it is shown that leadership behaviour in team settings is complex and the relationships between the influencing factors are closer than expected. Therefore, the study contributes to the general research by laying the groundwork for a more holistic approach to leadership. Moreover, it introduces personality as one of the most important factors influencing leadership behaviour. Closing the thesis pathways for future research and managerial as well as theoretical implications are given.
Keywords: Shared Leadership; Co-Leadership; Team Leadership; Healthcare; Germany; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|; fi=Digitaalinen media|en=Digital media|